A library of electrophysiological responses in plants - a model of transversal education and open science - Danae Madariaga; Derek Arro; Catalina Irarrázaval; Alejandro Soto; Felipe Guerra; Angélica Romero; Fabián Ovalle; Elsa Fedrigolli; Thomas DesRosiers; Étienne Serbe-Kamp; Timothy Marzullo (Plant Signaling & Behavior, 2024)
Electrophysiology in plants is understudied, and, moreover, an ideal model for student inclusion at all levels of education. Here, we report on an investigation in open science, whereby scientists worked with high school students, faculty, and undergraduates from Chile, Germany, Serbia, South Korea, and the USA. The students recorded the electrophysiological signals of >15 plant species in response to a flame or tactile stimulus applied to the leaves. We observed that approximately 60% of the plants studied showed an electrophysiological response, with a delay of ~ 3-6 s after stimulus presentation. In preliminary conduction velocity experiments, we verified that observed signals are indeed biological in origin, with information transmission speeds of ~ 2–9 mm/s. Such easily replicable experiments can serve to include more investigators and students in contributing to our understanding of plant electrophysiology.